Adherence to Antiretroviral Therapy among Hiv-Infected Children Attending Hiwot Fana and Dil-Chora Art Clinic at Referral Hospitals in Eastern Ethiopia - Samson Zegeye; Endalew Gemechu Sendo2 (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2015)
Background: The success of antiretroviral therapy (ART) depends on a high level of adherence to a life-long regimen of antiretroviral drugs (ARVs). Adherence is a concern in children because of factors relating to children such as age, disclosure status of HIV sero- status, and understanding of the medication. Few studies have determined the level of adherence of ART among children since the scale-up of access to ARVs in the study areas. This study was thus undertaken to determine the level of ART adherence among pediatric pat ients at an ART clinic, the reasons for non-adherence, and the factors associated with adherence, according to mothers/caregivers' reports. Methods: Hospital based cross-sectional descriptive study design combining quantitative and qualitative methods was used. Three hundred thirteen HIV‑positive children attending the ART center of referral hospitals were recruited in this study. The study was conducted from January - February 2013.An interviewer administered questionnaire was used to collect data. Data were entered in the Epi info software version 3.5.1 and then exported to the SPSS version 16 for quantitative analysis. Results: Adherence to ART in 313 HIV positive children during the past three and seven days was assessed,and 310 (99%) and 304 (97%) of them took greater than 95% of the total prescribed doses, respectively.According to the care givers' report,the average rate of adherence to ART among children as 284 (90.7%) in the one month recall period prior to the study. Disclosure of the child's sero status to the child, age of the child, occupational status, caregiver's relationship with child, and caregiver's knowledge of ARV treatment were factors independently associated with adherence to ART. Conclusion: The current study showed that the level of adherence to antiretroviral therapy was found to be high. Health care providers should reinforce adherence counseling during follow up and address proper usage of medication reminders. Further study on adherence rate and its determinants with multiple adherence measurements to determine the barriers to adherence is also recommended.